AWARENESS AND ATTITUDES OF PRIMARY HEALTHCARE PHARMACISTS REGARDING THE EFFICACY AND SIGNIFICANCE OF STEM CELL APPLICATIONS FOR MEDICAL PURPOSES-Qualitative prospective study - Nikolic Turnic, Tamara; Aksentijevic, Marija; Mikerova, Maria; Reshetnikov, Vladimir (Medicinski časopis, 2026)
Introduction: In recent years, interest in the collection and preservation of umbilical cord blood stem cells has increased substantially, owing to their therapeutic potential in a range of medical conditions. As highly accessible healthcare professionals, primary care pharmacists are frequently consulted on diverse medical issues. Consequently, it is imperative that they possess comprehensive knowledge—including a thorough understanding of stem cell applications—and engage in ongoing professional development.Objective: This study aimed to assess the awareness, attitudes, and opinions of licensed pharmacists working in primary healthcare regarding the medical use of stem cells.Methods: A cross-sectional survey was conducted using anonymous questionnaires distributed to pharmacists in primary healthcare settings across the Central part of Serbia. Data was collected from July 1 to August 1, 2022, and analyzed using IBM SPSS Statistics and MS Excel. Inclusion criteria encompassed current employment as a primary healthcare pharmacist in Serbia and voluntary informed consent to participate in the study.Results: A total of 248 pharmacists participated, the majority being female and employed in private healthcare institutions. The analysis revealed statistically significant differences in awareness, attitudes, or opinions between pharmacists working in the public and private sectors, except for a significant difference regarding knowledge of the existence of a stem cell donor registry (p
Keywords: stem cells, regenerative medicine, pharmacists, attitudes, primary healthcare